2010
DOI: 10.3109/00016349.2010.513427
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of mifepristone and misoprostol in second trimester pregnancy termination

Abstract: multiparous women and women with early gestation complete medical termination faster. Multiparity and shorter gestation time are also associated with lesser need for opiate analgesia, compared to nulliparous women or longer gestation time (≥ 17 weeks).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…33 The only 24-hour interval study using a 200-microgram misoprostol dosing (400 micrograms buccal misoprostol followed by 200 micrograms buccal every 6 hours) reported similar results as the longer interval studies at this dosage with a median induction time of 10 hours and 97% expelled by 24 hours. 21,[36][37][38][39][40][41] The two remaining observational studies used 400 micrograms misoprostol every 3-6 hours. One retrospective cohort showed a significant difference between 1-day and 2-day mifepristone-misoprostol intervals, using misoprostol 400 micrograms vaginally every 3 hours, with median induction times of 9.8 compared with 7.5 hours, respectively (P,.01) with no difference in the percent expelled at 24 hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The only 24-hour interval study using a 200-microgram misoprostol dosing (400 micrograms buccal misoprostol followed by 200 micrograms buccal every 6 hours) reported similar results as the longer interval studies at this dosage with a median induction time of 10 hours and 97% expelled by 24 hours. 21,[36][37][38][39][40][41] The two remaining observational studies used 400 micrograms misoprostol every 3-6 hours. One retrospective cohort showed a significant difference between 1-day and 2-day mifepristone-misoprostol intervals, using misoprostol 400 micrograms vaginally every 3 hours, with median induction times of 9.8 compared with 7.5 hours, respectively (P,.01) with no difference in the percent expelled at 24 hours.…”
Section: Resultsmentioning
confidence: 99%
“…With total abortion times (mifepristone to expulsion), the wait time between mifepristone and misoprostol warrants consideration, because it strongly correlates with total time (Fig. 23,24,35,36,40,41 This should be considered when applying results to higher gestational ages and patients should be counseled appropriately. For example, Chai et al 22 reported the overall success rate for abortion 24 hours after first misoprostol administration was 91.5% for immediate misoprostol dosing compared with 100% in the 36-to 38-hour group.…”
Section: Discussionmentioning
confidence: 99%
“…Misoprostol is an effective uterotonic drug for induction of labor [2]. Its performance depending on multiple doses, frequency, and routes of administration (vaginal, oral, and sublingual) has been investigated in previous studies [11][12][13][14][15]. Most studies have emphasized the success of this drug when it is administered vaginally at high dose.…”
Section: Discussionmentioning
confidence: 98%
“…Various regimens of misoprostol use in terms of route, dosage, interval or combination of mifepristone have been tested to determine the optimal application in enhancing the efficacy of pregnancy termination. Some non‐randomized controlled trials suggest that the combination of mifepristone with misoprostol have a very high efficacy for pregnancy termination . Although there are some randomized control trials (RCT) in the recent literature showing that the combination of mifepristone and misoprostol is more effective, mifepristone is illegal in Thailand and thus unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…Some non-randomized controlled trials suggest that the combination of mifepristone with misoprostol have a very high efficacy for pregnancy termination. [6][7][8][9] Although there are some randomized control trials (RCT) in the recent literature showing that the combination of mifepristone and misoprostol is more effective, 10 mifepristone is illegal in Thailand and thus unavailable. Misoprostol is the most widely used medication for medical abortion in Thailand.…”
Section: Introductionmentioning
confidence: 99%